A közút tartozéka: egy sajátos jogintézmény ellentmondásai - Pribula, László (Debreceni Jogi Műhely, 2009)
In the legal terminology of private law several times the same definition is used for addressing the same legal institution (e.g. default penalty, in-building). In most of the cases there is no problem to separate these institutions and we can also give an explanation why legislator used the same terminology. The definition of accessory is used for a special group of article groups in the Hungarian Civil Code and also used in the Act I. of 1988. From the angle of judicature it is problematic as even if the definition of road accessory is build upon the general terminology of accessory in the Civil Code, the two legal institutions are not the same. In the essay we would like to emphasize that the safety of traffic does not give a decent reason why we have to restrict the proprietary rights with using the institution of road accessory. This restriction is in a close connection with not only the distance from the public road but the effect of the property to the safety of traffic. The valid regulations may cause illogical contradictions and judicature problem.